Can macrophyte harvesting from eutrophic water close the loop on nutrient loss from agricultural land?. (1st April 2015) - Quilliam, Richard S.; van Niekerk, Melanie A.; Chadwick, David R.; Cross, Paul; Hanley, Nick; Jones, Davey L.; Vinten, Andy J.A.; Willby, Nigel; Oliver, David M.
Abstract: Eutrophication is a major water pollution issue and can lead to excessive growth of aquatic plant biomass (APB). However, the assimilation of nutrients into APB provides a significant target for their recovery and reuse, and harvesting problematic APB in impacted freshwater bodies offers a complementary approach to aquatic restoration, which could potentially deliver multiple wider ecosystem benefits. This critical review provides an assessment of opportunities and risks linked to nutrient recovery from agriculturally impacted water-bodies through the harvesting of APB for recycling and reuse as fertilisers and soil amendments. By evaluating the economic, social, environmental and health-related dimensions of this resource recovery from 'waste' process we propose a research agenda for closing the loop on nutrient transfer from land to water. We identify that environmental benefits are rarely, if ever, prioritised as essential criteria for the exploitation of resources from waste and yet this is key for addressing the current imbalance that sees environmental managers routinely undervaluing the wider environmental benefits that may accrue beyond resource recovery. The approach we advocate for the recycling of 'waste' APB nutrients is to couple the remediation of eutrophic waters with the sustainable production of feed and fertiliser, whilst providing multiple downstream benefits and minimising environmental trade-offs. This integrated 'ecosystem services approach' has the potential to holistically close the loop on agricultural nutrient loss, and thus sustainably recover finite resources such as phosphorus from waste. Highlights: Harvesting Aquatic Plant Biomass (APB) can remediate eutrophic waters. Nutrients assimilation into Aquatic Plant Biomass (APB) can be recovered and reused. Harvesting Aquatic Plant Biomass (APB) can close the loop on agricultural nutrient loss. This approach can also provide multiple downstream ecosystem services.